(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2025)
India, the world’s largest democracy, frequently engages in electoral exercises to uphold the principles of governance and representation. However, the fragmented election cycles of the Lok Sabha (House of the People) and State Legislative Assemblies pose significant challenges, including substantial financial costs, administrative burdens, and policy disruptions. The concept of One Nation, One Election (ONOE) has emerged as a proposed electoral reform to synchronize national and state elections, aiming to address these challenges. This article examines the potential of ONOE in transforming India’s electoral landscape. It delves into the historical context of simultaneous elections, which were practiced from 1952 to 1967, and analyzes the factors that led to their discontinuation. The study explores the potential benefits of ONOE, such as cost efficiency, continuity in governance, reduction in electoral fatigue, and enhanced voter participation. Simultaneously, the article addresses the critical challenges associated with this proposal, including its implications for federalism, the logistical hurdles in synchronization, and the need for extensive constitutional amendments. Furthermore, it considers the potential marginalization of regional and smaller political parties in a unified electoral framework. Drawing on comparative experiences from countries with synchronized elections and a detailed examination of India’s political and constitutional framework, the article provides policy recommendations for phased implementation, consensus building, and infrastructural improvements. It concludes that while ONOE holds promise for improving governance and efficiency, it requires a nuanced approach that respects India’s diversity and federal principles. By evaluating the opportunities and challenges of ONOE, this study contributes to the ongoing discourse on electoral reforms in India and offers insights for policymakers, academics, and stakeholders interested in enhancing the democratic process.